2006
DOI: 10.1091/mbc.e05-11-1094
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Akt in ER-to-Golgi Transport of SCAP/SREBP: A Link between a Key Cell Proliferative Pathway and Membrane Synthesis

Abstract: Akt is a critical regulator of cell growth, proliferation, and survival that is activated by phosphatidylinositol 3-kinase (PI3K). We investigated the effect of PI3K inhibition on activation of sterol regulatory element binding protein-2 (SREBP-2), a master regulator of cholesterol homeostasis. SREBP-2 processing increased in response to various cholesterol depletion approaches (including statin treatment) and this increase was blunted by treatment with a potent and specific inhibitor of PI3K, LY294002, or whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
122
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(132 citation statements)
references
References 52 publications
8
122
1
1
Order By: Relevance
“…It is possible that the sustained overstimulation of the PI3K pathway by myr-Akt activates to saturation the HMGR promoter by a CRE-independent mechanism. In this way, it is interesting to point out that PI3K/Akt pathway activation in Chinese hamster ovary cells promotes as well the transcription of the HMGR promoter by stimulating SREBP processing and ERto-Golgi transport of SCAP (28). In summary, our data support the tenet that the activation of the PI3K pathway by extracellular signaling molecules up-regulates cholesterol biosynthesis in myelin-forming cells, both by CRE-dependent and CRE-independent mechanisms.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It is possible that the sustained overstimulation of the PI3K pathway by myr-Akt activates to saturation the HMGR promoter by a CRE-independent mechanism. In this way, it is interesting to point out that PI3K/Akt pathway activation in Chinese hamster ovary cells promotes as well the transcription of the HMGR promoter by stimulating SREBP processing and ERto-Golgi transport of SCAP (28). In summary, our data support the tenet that the activation of the PI3K pathway by extracellular signaling molecules up-regulates cholesterol biosynthesis in myelin-forming cells, both by CRE-dependent and CRE-independent mechanisms.…”
Section: Discussionsupporting
confidence: 71%
“…However, we also found that the deletion of the CRE in the HMGR reductase promoter did not reduce the myr-Akt-dependent transcriptional activity (Fig. 5d), suggesting that the sustained activation of Akt is able to induce the HMGR promoter at saturation level by a CREindependent mechanism (28).…”
Section: Intracellular Pathways Involved In Neuregulin 1 Signaling-mentioning
confidence: 71%
“…Gene expression levels of Insig-1, Insig-2, and DHCR7 were determined and normalized to the housekeeping gene porphobilinogen deaminase (PBGD). Primer sequences for PBGD have been published previously (22,23). Insig-1 primer sequences were CGCCTGTTGCAGAGGAGCC (forward) and CGAGGTGACTGTCGATACAGGG (reverse), Insig-2 primers were CGCTCTTTCCACCTGATGTG (forward) and CAGTCCAATGGATAGTGCAGCC (reverse), and DHCR7 primers were CACCGGCCGTGCTAGTCTGG (forward) and CAGGCTTGTAGCCCGTTCACCTC (reverse).…”
Section: Methodsmentioning
confidence: 99%
“…Insulin signaling activates AKT, which has been reported to be directly involved in the movement of SREBP-SCAP from the ER to Golgi ( Fig. 2; Du et al 2006;Yellaturu et al 2009). The precursor SREBP-1c protein is also a substrate for AKT phosphorylation in vitro (Yellaturu et al 2009).…”
Section: Srebp Regulation By Insulinmentioning
confidence: 99%